Multi-objective optimization of a double tapered flow field Proton Exchange Membrane Fuel cell - Emad Farokhi; Mehrdad Ghasabehi; Mehrzad Shams (Energy Reports, 2023)
Flow fields are essential in Proton Exchange Membrane Fuel Cell (PEMFC) performance. Appropriate in-plane tapering in the main channels width of parallel flow fields enhances flow distribution uniformity, increasing performance. To the best of the authors, there is no literature discussing the through-plane inclination in a parallel flow field with in-plane tapered main channels. This study develops a surrogate model based on a data set to study double tapering in the flow field. The three-dimensional multiphase Computational Fluid Dynamics (CFD) generates the data set. Decision variables are the angle of depth tapering, operating pressure, temperature, stoichiometries, and voltage. Also, the objectives are power density and efficiency. Proper depth tapering increases mass transfer, decreasing the concentration loss. The increment of 19.6% in maximum power is captured by tapering. Depth tapering in the parallel flow field improves efficiency, especially at a higher temperature and lower pressure. Furthermore, a multi-layer multi-objective optimization methods are utilized. A reference depth tapering angle θ is defined. Optimum characteristics are the tapering angle of 0.13θ, the temperature of 329.9 K, the operating pressure of 4 atm, the operating voltage of 0.465 V, and the unit stoichiometry of both sides. Optimum characteristics bring the best performance, an efficiency of 21.55%, and a power density of 0.75 W cm−2.